1975
DOI: 10.1128/jb.124.1.491-496.1975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations in the qa gene cluster of Neurospora crassa on the enzyme catabolic dehydroquinase

Abstract: Catabolic dehydroquinase, which functions in the inducible quinic acid catabolic pathway of Neurospora crassa, has been purified from wild type (74-A) and three mutants in the qa gene cluster. The mutant strains were: 105c, a temperature-sensitive constitutive mutant in the qa-1 regulatory locus; M-16, a qa-3 mutant deficient in quinate dehydrogenase activity; and 237, a leaky qa-2 mutant which possess very low levels of catabolic dehydroquinase activity. The enzymes purified from strains 74-A, 105c, and M-16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…(i) C-DHQase. C-DHQase (encoded by the qa-2+ gene) was further characterized in studies of the purified enzyme from the wild type, certain qa-2 mutants, and other mutants with mutations in other genes (qa-Jc and qa-3-) of the qa cluster (10,26,30). These studies concluded that the purified wild-type enzyme possesses several unusual structural, physical, and biochemical properties, e.g., a very high specific activity, a high degree of stability in the presence of a variety of denaturing conditions (including high temperatures) and reagents, and a polymeric structure with a molecular weight of ca.…”
Section: Downloaded Frommentioning
confidence: 99%
“…(i) C-DHQase. C-DHQase (encoded by the qa-2+ gene) was further characterized in studies of the purified enzyme from the wild type, certain qa-2 mutants, and other mutants with mutations in other genes (qa-Jc and qa-3-) of the qa cluster (10,26,30). These studies concluded that the purified wild-type enzyme possesses several unusual structural, physical, and biochemical properties, e.g., a very high specific activity, a high degree of stability in the presence of a variety of denaturing conditions (including high temperatures) and reagents, and a polymeric structure with a molecular weight of ca.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The fourth gene, qa-1, encodes a regulatory protein that, in the presence of inducer (quinic acid), acts in a positive fashion to initiate coordinate synthesis of the three qa enzymes (3)(4)(5)(6). Evidence supporting this hypothesis has come from comparative studies of purified catabolic dehydroquinase (7) obtained from the wild type and from mutants bearing lesions in the qa gene cluster (9). These studies indicate that the properties of purified catabolic dehydroquinase obtained from the wild type and from mutants with lesions in the qa-1 gene or the qa-3 gene are identical, as predicated by the hypothesis.…”
mentioning
confidence: 86%
“…These studies indicate that the properties of purified catabolic dehydroquinase obtained from the wild type and from mutants with lesions in the qa-1 gene or the qa-3 gene are identical, as predicated by the hypothesis. In contrast, the catabolic dehydroquinase from one qa-2 mutant (M237) was found to be 1,500-fold less active and appeared to have a slightly different amino acid content (9). Despite the low activity, this mutant was shown to be immunologically competent in tests with antisera against catabolic dehydroquinase and to have wild-type levels of catabolic dehydroquinase protein.…”
mentioning
confidence: 90%